In vitro activity to promote plant growth and biological control of rhizobacteria isolated from bermuda grass ruderal - Moreno Salazar, Sergio Francisco; Rentería Martínez, María Eugenia; Ochoa Meza, Andrés; Guzmán Ortíz, Juan Manuel; Fernández Herrera, Ernesto; Barrera Silva, Miguel Ángel (Revista Mexicana de Ciencias Agrícolas, 2019)
Currently, the use of plant growth promoting bacteria is a viable alternative to the indiscriminate use of agrochemicals. In order to obtain bacteria with the capacity to promote plant growth, in this work twelve strains with nitrogen fixation activity were isolated from the rhizosphere of bermuda grass (Cyonodon dactylon) ruderal. Based on the speed and intensity of the color change in the qualitative nitrogen fixation test, two isolates were selected for molecular identification and characterization. The amplification, sequencing and analysis of 16S rRNA ribosomal gene fragments allowed to identify Pseudomonas monteilii (Pm0710) and Chryseobacterium massiliae ca (Cm0711). Both isolates showed phosphate solubilization activity, production of indole-3-acetic acid, gibberellic acid and siderophores, alkaline phosphatase and ACC deaminase, as well as inhibition against: Fusarium brachygibbosum, F. falciforme, F. oxysporum and Ceratobasidium sp. Although Cm0711 was significantly higher than Pm0710 in most of the properties analyzed, the two bacteria have potential to be used as bio-inoculants; however, before validation must be done in vivo.
Keywords: Ceratobasidium; Chryseobacterium massiliae; Fusarium; Pseudomonas monteilii; PGPR